Seroprevalence of SARS-CoV-2 antibody among healthcare workers in a university hospital in Mallorca, Spain, during the first wave of the COVID-19 pandemic. (April 2021) - Rodriguez, Adrian; Arrizabalaga-Asenjo, Maria; Fernandez-Baca, Victoria; Lainez, Maria Pilar; Al Nakeeb, Zaid; Garcia, Jose Daniel; Payeras, Antoni
Highlights: The seroprevalence of antibodies against SARS-CoV-2 in our university hospital in Mallorca, Spain, is around 2.8%. The seroprevalence was slightly higher in nurses, wardens and registrars. Those participants with positive antibody test results had been in closer contact with COVID-19 subjects. The most commonly experienced symptoms by the hospital care workers were fever, cough, asthenia, and anosmia. Abstract: Objective: To estimate the SARS-CoV-2 antibody seroprevalence in healthcare workers (HCWs) at a university hospital in Mallorca, Spain. Methods: All HCWs received an e-mail inviting them to take part in the study. Participants had a nasopharyngeal swab test performed for reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) and serological tests to detect SARS-CoV-2 antibodies (primary study). Additionally, they were invited to complete a questionnaire on their exposure to COVID-19 individuals and their COVID-19-related symptoms (secondary study). Prevalence of antibodies (IgG, IgM, or both) and 95% confidence intervals (CIs) were calculated. Results: Seventy-nine percent of the hospitalʼs HCWs (N = 2210) took part in the primary study. Antibodies were detected in 61 participants, a prevalence of 2.8% (95% CI: 2.5–3.1). The prevalence was slightly higher in nurses (3.4%), registrars (3.9%), and wardens (3.4%). Thirty-nine percent of the primary study participants completed the secondary study questionnaire. Those with positive antibody test results had closer contact with COVID-19 individuals (60% vs. 92%; p < 0.001). Conclusion: After the first wave of the COVID-19 pandemic in Spain, the seroprevalence of SARS-CoV-2 antibodies in our university hospital HCWs was around 2.8%, which is slightly higher than the seroprevalence in the general population in our region. We believe it would be advisable to perform additional seroprevalence studies during the second wave of the epidemic.